THE IMPLEMENTATION OF DAKWAH BIL HAL BY THE MUHAMMADIYAH DISASTER MANAGEMENT CENTER OF NORTH SUMATRA IN BUILDING COMMUNITY MORALITY - Cipta Novian; Azhar (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Moral misconduct among children and adolescents is a social issue increasingly garnering public attention. In Manunggal Village, Labuhan Deli District, Deli Serdang Regency, various forms of moral misconduct involving minors have been identified, including drug abuse and involvement in online gambling. These conditions are driven by factors such as peer environments, a lack of family supervision, uncontrolled technological advancements, and limited positive activities for adolescents. These issues prompted the Muhammadiyah Disaster Management Center of North Sumatra to intervene using the dakwah bil hal (preaching through action) approach, acting as a facilitator and community partner in efforts to restore the morality of children and adolescents. Research findings indicate that the dakwah bil hal implemented by MDMC North Sumatra was realized through various activities: field observations, mapping of social issues, awareness-raising regarding the dangers of drugs and online gambling, family support, youth guidance, coordination with village officials and community leaders, and program monitoring and evaluation. All activities prioritized community participation, ensuring that the community was not merely a program recipient but an integral part of the transformation process. This approach yielded positive impacts, including heightened public awareness of the dangers of drugs and online gambling, an enhanced role for families in guiding their children, increased community concern for the morality of the younger generation, and greater participation by children and adolescents in social and religious activities.